A round-robin test of thermal desorption spectroscopy with quadrupole mass spectrometers calibrated by standard conductance element. (March 2015) - Yoshida, Hajime; Arai, Kenta; Fujii, Kenichi
Highlights: Results of a round-robin test of thermal desorption spectroscopy are reported. Three testing laboratories participated in this round-robin test. QMS of each participant was calibrated in-situ by a standard conductance element. The total desorption amounts from test samples show agreement within about 10%. Abstract: The results of a round-robin test of thermal desorption spectroscopy (TDS) in which the quadrupole mass spectrometer of each participant was calibrated in-situ by a standard conductance element are reported. The desorption rate from three commercially available reference materials was quantified from the calibration results, and compared among the three participants. The total reported desorption amounts of hydrogen and argon molecules from the reference materials showed agreement within about 10%. The degree of equivalence of three TDS apparatuses was discussed. It is also shown that the quantification of the gas desorption amounts yields us the appropriate relative ratio between desorbed gas species.